Folded Forehead Flaps For Reconstruction Of Cheek Defects - Dr. R. Bharat; Dr. K. Ramakrishnan Nair; Dr. O. J. Jacob; Dr. U. R. Nandakumar (Indian Journal of Plastic Surgery)
The temporal forehead flap is a useful flap for reconstruction of cheek defects. Experience of ten cases is being presented where folded forehead flaps were used for reconstruction of post-excisional full thickness cheek defects. It has been found that it is quite a simple, safe and satisfactory method involving the use of a single flap.